Retest reliability of measuring hip extensor muscle strength in different testing positions in young people with cerebral palsy - Dodd Karen J; Taylor Nicholas F; Dyball Kate M (BMC, 2011)
Abstract Background In young people with spastic diplegic cerebral palsy weakness of the hip extensor muscles are associated with limitations in activity. It is important that clinicians can reliably measure hip extensor muscle strength to monitor changes over time and the effects of any interventions. Previous research has demonstrated high reliability for measuring strength of all muscles of the lower limb, with the exception of the hip extensors. Therefore the aim of this study was to examine the retest reliability of measuring hip extensor strength in young people with cerebral palsy. Methods Using a test-retest reliability research design, 19 participants with spastic diplegic cerebral palsy (Gross Motor Function Classification System Levels II and III) (mean 19 y 2 mo [S D 2 y 5 mo]) attended two testing sessions held 12 weeks apart. Three trials with a hand-held dynamometer were taken at each testing session in supine, prone and standing. Retest reliability was calculated with Intraclass Correlation Coefficients (ICC(2,1)) and with units of measurement (kilograms) converted to a percentage strength change. Results ICC values ranged from .74 to .78 in supine, .75 to .80 in prone, and .73 to .75 in standing. To be 95% confident that real change had occurred, an individual's strength would need to increase 55 to 60% in supine, 86 to 102% in prone, and 102 to 105% in standing. To be 95% confident that real change had occurred across groups, strength would need to increase 4 to 8% in supine, 22 to 31% in prone, and 32% to 34% in standing. Higher ICC values were observed when three trials were used for testing. Conclusions The supine testing position was more reliable than the prone or standing testing positions. It is possible to measure hip extensor strength with sufficient reliability to be able monitor change within groups using the supine position provided three trials are used during testing. However, there is insufficient reliability to monitor changes in hip extensor strength in individuals with cerebral palsy unless they exhibit very large strength increases.